2018
DOI: 10.3389/fphar.2018.01007
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin May Significantly Improve Postoperative Cognitive Function of Elderly Patients Undergoing Spinal Surgery by Reducing the Translocation of Lipopolysaccharide and Systemic Inflammation

Abstract: Background: Studies have shown that perioperative inflammatory response is one of the important factors that caused postoperative cognitive dysfunction (POCD). Ulinastatin is a broad-spectrum protease inhibitor that inhibits inflammatory. We investigated the effects of ulinastatin on inflammatory response and early postoperative cognitive function in elderly patients undergoing spinal surgery.Methods: This clinical trial was approved by the Xuanwu Hospital Ethical Committee (Registration number: ChiCTR-IPR-160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…As reported, POCD occurs in 65% of patients discharged after CABG surgery and in ∼40% in the months following surgery on average [22]. The 21-day POCD incidence of 27.1% in the present study is similar with previous reports [23][24][25]. RDW suggests the heterogeneity of red blood cell size, and reflects the relative number and function of red blood cells.…”
Section: Discussionsupporting
confidence: 89%
“…As reported, POCD occurs in 65% of patients discharged after CABG surgery and in ∼40% in the months following surgery on average [22]. The 21-day POCD incidence of 27.1% in the present study is similar with previous reports [23][24][25]. RDW suggests the heterogeneity of red blood cell size, and reflects the relative number and function of red blood cells.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have investigated whether inhibiting the hippocampus neuroinflammation or interrupting related signaling pathway improves the brain function in other regions. In one of our clinical studies, we reported improvements in cognitive test performance after anti-inflammatory treatment in elderly patients following spinal surgery (Zhang et al, 2018 ). However, rs-fMRI was not applied in this study so the function in other brain regions could not be fully assessed.…”
Section: Discussionmentioning
confidence: 96%
“…The eventual choice of anesthetic regimen (general anesthesia or neuraxial block) was based on the preference and experience of the anesthesiologist alongside discussion with the patient and their family. A uniform anesthetic regimen was conducted based on previous studies of orthopedic operations in older adults (Zhang et al, 2018). In order to minimize postoperative pain, a second fascia iliac block with the aforementioned protocol was provided right before anesthesia regardless of the anesthetic regimen.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%